Non linear electromagneto-optical effect in epitaxial films of yttrium iron garnet - Koronovskyy, V.E. (Functional Materials, 2006)
The magneto-electric effect has been studied both in multidomain areas and in local areas of single domains in epitaxial films of yttrium iron garnet using optical polarimetry method. The effect has been revealed to met a square law with respect to electric field and its magnetic field dependences have been investigated. Local effects from single magnetic domains have been registered and it has been found that those are defined by local distributions of magnetic induction in the probing points. It has been shown that the film magnetization remains unchanged due to application of an external electric field, and the revealed features of magnetic field dependences are caused by the domain film structure sensitivity to changes in magnetic anisotropy induced by an external electric field.